Posicionamento de vendas de produtos e serviços pelas concessionárias distribuidoras de energia e a modicidade tarifária - Maciel, Ivana Maria Oliveira (2006)
The commercialization of products and services by power utility companies related to the electric energy supply depends on the strategies adopted by the companies to position themselves in the market. This dissertation addresses issues regarding the application of these strategies, focusing particularly on the accounting of these sales as Other Revenues. Such sales contribute to the tariff s moderateness, which is one of the pillars of the electric sector model implanted in 2003, as they are discounted in the tariff revisions. The primary and main source of data for this work are: the "Methodology of allocation of Non-concession Revenues in the revenue of the basic service of the public hydro companies , discussed in the Public Audience no. 014/2003 of the Superintendence of Economic Regulation (SRE/ANAEEL); Technical Note 052/ANEEL 2003; the Draft Technical Note no. 167/ANEEL/2006 and data supplied by the Bahia State Power Utility Company (Coelba). This work analyzes the laws identified as pertinent to this theme, as well as the Technical Notes issued by either the Concessionary Authority or the Regulatory Agent and data from electric distribution companies websites. It also collects specific qualitative data from Coelba in the following areas that comprised the case study: large customers, market, accounting, regulation and marketing. The analysis of all these elements intended to: (a) verify whether the recommendations of the regulatory agency ANEEL have been applied when the Agency revised the tariffs of electric distribution companies and (b) establish a comparison between the existing orientation and the proposal to be submitted to a Public Audience. The conclusion is that the concepts of the methodology professed by the regulatory agency have not been applied consistently. Starting from that, this work recommends a new classification and a mechanism to split the gains generated by the Other Revenues between consumers and power utilities, which should result in a more moderate tariff and an increase of both customer satisfaction and the electric distribution company s remuneration, with consequent regional development of the concession.